Molecular and serological infection marker screening in blood donors indicates high endemicity of hepatitis E virus in Poland. Issue 5 (1st March 2018) - Grabarczyk, Piotr; Sulkowska, Ewa; Gdowska, Jolanta; Kopacz, Aneta; Liszewski, Grzegorz; Kubicka‐Russel, Dorota; Baylis, Sally A.; Corman, Victor M.; Noceń, Ewa; Piotrowski, Dariusz; Antoniewicz‐Papis, Jolanta; Łętowska, Magdalena
Abstract : BACKGROUND: Until now, markers of hepatitis E virus (HEV) infection have not been studied in blood donors throughout Poland, and no acute case of HEV infection has been closely documented or confirmed by HEV RNA detection. The prevalence of HEV infection markers, including HEV RNA in Polish blood donors and virus genotypes was investigated. STUDY DESIGN AND METHODS: In total, 12, 664 individual donations from 22 Polish blood transfusion centers were tested for HEV RNA by transcription‐mediated amplification. In addition, 3079 first‐time donors sampled throughout Poland also were screened for antibodies to HEV. HEV RNA and immunoglobulin M‐positive donations were confirmed using real‐time reverse transcription‐polymerase chain reaction and Western blotting, respectively. RESULTS: Ten donors were identified as RNA initial reactive (one of 1266 donors), and six (one of 2109) were identified as repeat reactive and confirmed by real‐time reverse transcription‐polymerase chain reaction or seroconversion. Sequence analysis identified HEV Genotype 3c in one donor and Genotype 3i in two others. On average, 43.5% of donors were immunoglobulin G‐positive. Immunoglobulin G seroprevalence ranged from 22.7% to 60.8% in group ages 18 to 27 years and 48 to 57 years, respectively and differed between administrative regions from 28.9% in Podlasie to 61.3% in Wielkopolska. Thirty‐nine of the donors were immunoglobulin M‐positive, and seven donors were IgM positive only (0.2%). Of 37 immunoglobulin M‐reactive samples tested by Western blot, 24 (64.9%) were confirmed. CONCLUSIONS: The current results indicate a high level of HEV endemicity throughout Poland compared with other countries. There is an urgent need to consider the protection of recipients of blood components against transfusion‐transmitted HEV infection.